"I just want to word it better": developing disciplinary literacies in an after-school spoken word poetry team. Issue 1 (14th February 2022) - Lesus, Melina; Vaughan, Andrea
Abstract : Purpose: This study aims to explore how youth poets wrote in a community of practice and how their out-of-school poetry writing contributed toward developing disciplinary literacy. Design/methodology/approach: In this qualitative case study, the authors studied youth's writing by drafting narrative field notes, collecting student writing and process drawings and interviewing participants. Findings: The authors found that the poets in this study maintained ownership of their writing and engaged in writing processes in ways that reflected Behizadeh's (2019) conception of authenticity as writing that connects both to students' experiences, and to the purposes and audiences of their writing context. Practical implications: This out-of-school context provides implications for how English Language Arts teachers can rethink what disciplinary literacy looks like in classroom writing instruction. Originality/value: By maintaining ownership of their writing, the youth agentively positioned themselves not only as students accumulating disciplinary knowledge but also as participants in a community of practice.